2010
DOI: 10.1155/2010/752381
|View full text |Cite
|
Sign up to set email alerts
|

Antigen-Specific Polyclonal Cytotoxic T Lymphocytes Induced by Fusions of Dendritic Cells and Tumor Cells

Abstract: The aim of cancer vaccines is induction of tumor-specific cytotoxic T lymphocytes (CTLs) that can reduce the tumor mass. Dendritic cells (DCs) are potent antigen-presenting cells and play a central role in the initiation and regulation of primary immune responses. Thus, DCs-based vaccination represents a potentially powerful strategy for induction of antigen-specific CTLs. Fusions of DCs and whole tumor cells represent an alternative approach to deliver, process, and subsequently present a broad spectrum of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…To date, several strategies have been assessed for creating DC-based cancer vaccines, including: (1) loading DCs with defined TAAs, which is the most commonly applicable strategy, for DC-based vaccination, but has a number of drawbacks [ 45 ]; (2) pulsing DCs with tumor DNA/RNA; and (3) generating fusions of DCs and tumor cells. DC/glioma-specific peptides have been confirmed to be a useful strategy to elicit CTL responses and have been shown to be more effective than other types of DC-based vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several strategies have been assessed for creating DC-based cancer vaccines, including: (1) loading DCs with defined TAAs, which is the most commonly applicable strategy, for DC-based vaccination, but has a number of drawbacks [ 45 ]; (2) pulsing DCs with tumor DNA/RNA; and (3) generating fusions of DCs and tumor cells. DC/glioma-specific peptides have been confirmed to be a useful strategy to elicit CTL responses and have been shown to be more effective than other types of DC-based vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…These cells possibly express all TAs and combine it with the immune stimulatory capacities of APCs ( 17 , 42 ). Immunity might be enhanced because different TAs may induce different immune effector mechanisms ( 50 , 51 ). Upon establishment of a vaccination protocol, the generation of tumor/DC-fusion hybrids may thus result in a simple form of personalized anti-cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Immune responses induced by fusion hybrids have mainly been associated with the induction of tumor-specific CTLs ( 51 ). We additionally observed a marked humoral immune response, which could contribute to efficient anti-tumor responses.…”
Section: Discussionmentioning
confidence: 99%
“…The strategy for DC/tumor fusion vaccine is based on the fact that DCs are the most potent antigen-presenting cells in the body, whereas tumor cells express abundant tumor antigens. In animal studies, DC/tumor fusion vaccines have been shown to possess the elements essential for processing and presenting tumor antigens to host immune cells, for inducing effective immune response, and for breaking T-cell tolerance to TAAs (Gong, Chen et al, 1997;Koido, Hara et al, 2007;Gong, Koido et al, 2008;Koido, Hara et al, 2009;Koido, Hara et al, 2010a;Koido, Homma et al, 2010b). Recently, we have reported that fusions of human pancreatic cancer cells and DCs induce CTL responses against pancreatic cancer cells in vitro (Koido, Hara et al, 2010a).…”
Section: Dc-based Vaccinesmentioning
confidence: 99%